2023
DOI: 10.3390/cancers15041271
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RNA Marker Panels for Circulating Tumor Cells and Evaluation of Their Prognostic Relevance in Breast Cancer

Abstract: Liquid biopsy is a promising tool for therapy monitoring of cancer patients, but a need for further research in this field exists in order to improve sensitivity, specificity, standardization and minimize costs. In our present study, we evaluated two panels of transcripts related with the presence of circulating tumor cells (CTCs) (Panel 1: CK19, EpCAM, SCGB2A2 and Panel 2: EMP2, SLC6A8, HJURP, MAL2, PPIC and CCNE2) in two cohorts of breast cancer patients (metastatic and early). A blood cell fraction possibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, at the individual marker level, a substantial level of concordance was only observed with the highly specific DLL3 and CK19 LC (Table S2) assays. The CK19 LC hybridization probe RT‐qPCR assay was introduced to minimize false positive samples, due to a very high specificity 25 . Compared to the CK19 TaqMan assay, the CK19 transcript was not amplified in any of the HD samples using the hybridization probe assay.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, at the individual marker level, a substantial level of concordance was only observed with the highly specific DLL3 and CK19 LC (Table S2) assays. The CK19 LC hybridization probe RT‐qPCR assay was introduced to minimize false positive samples, due to a very high specificity 25 . Compared to the CK19 TaqMan assay, the CK19 transcript was not amplified in any of the HD samples using the hybridization probe assay.…”
Section: Resultsmentioning
confidence: 99%
“…The CK19 LC hybridization probe RT-qPCR assay was introduced to minimize false positive samples, due to a very high specificity. 25 Compared to the TaqMan CK19 transcript was not amplified in any of the HD samples using the hybridization probe assay.…”
Section: Ctc-related Gene Transcripts With and Without Pre-amplificationmentioning
confidence: 89%
See 2 more Smart Citations
“…In a recent study, using RT-qPCR, two panels of transcripts related to the presence of CTCs (Panel 1: CK19 , EpCAM , SCGB2A2 and Panel 2: EMP2 , SLC6A8 , HJURP , MAL2 , PPIC and CCNE2 ), in two cohorts of breast cancer patients (metastatic and early), were evaluated. The findings indicated that Panel 2 markers that were not linked to an epithelial phenotype also provided important prognostic information [ 50 ].…”
Section: Ctc: Challenges For the Management Of Cancer Patientsmentioning
confidence: 99%